2017
DOI: 10.1038/s41598-017-13181-x
|View full text |Cite
|
Sign up to set email alerts
|

Unified treatment of spin torques using a coupled magnetisation dynamics and three-dimensional spin current solver

Abstract: A three-dimensional spin current solver based on a generalised spin drift-diffusion description, including the bulk and interfacial spin Hall effects, is integrated with a magnetisation dynamics solver. The resulting model is shown to simultaneously reproduce the spin-orbit torques generated using the spin Hall effect, spin pumping torques generated by magnetisation dynamics in multilayers, as well as the spin transfer torques acting on magnetisation regions with spatial gradients, whilst field-like and spin-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…It may be shown that under the assumption of negligible in-plane spin diffusion this expression is equivalent to Zhang-Li STTs as given in Eq. ( 2), 9,17,67 where the non-adiabaticity parameter is constant and given by β ffi λ 2 J /λ 2 sf in the limit of long spin dephasing length and long domain walls. The assumption of negligible in-plane spin diffusion breaks down for rapidly varying magnetization textures such as vortices and skyrmions, and this can lead to spatially varying and enhanced non-adiabaticity.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…It may be shown that under the assumption of negligible in-plane spin diffusion this expression is equivalent to Zhang-Li STTs as given in Eq. ( 2), 9,17,67 where the non-adiabaticity parameter is constant and given by β ffi λ 2 J /λ 2 sf in the limit of long spin dephasing length and long domain walls. The assumption of negligible in-plane spin diffusion breaks down for rapidly varying magnetization textures such as vortices and skyrmions, and this can lead to spatially varying and enhanced non-adiabaticity.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…Spin torques included in the magnetisation dynamics equation can be computed self-consistently using a drift-diffusion model 24,25 . Within this model the charge and spin current densities are given as:Here J S is a rank-2 tensor such that J S ij signifies the flow of the j component of spin polarisation in the direction i , J C is the charge current density, E is the electric field, S is the spin accumulation, and m is the normalised magnetisation.…”
Section: Spin Transport Modelmentioning
confidence: 99%
“…For an N/F interface with current in the plane, if diffusion effects are negligible, the drift-diffusion equations may be solved analytically to obtain the resulting interfacial spin torques due to SHE 25 . These are given as a combination of damping-like and field-like spin-orbit torques as:Here p = z × e Jc , where e Jc is the charge current direction.…”
Section: Spin Transport Modelmentioning
confidence: 99%
“…The coupled charge-spin-magnetization dynamics driven by the ac voltage is considered on the base of the diffusive model 28 31 . The free charge density current is described in the metal layers by the equation: which includes contributions from electron drift driven by electric field , diffusion driven by the gradient of free charge density and a diffusive spin polarisation representing spin conductivity contribution, respectively.…”
Section: The Modelmentioning
confidence: 99%
“…Although we implemented both spin-dependent surface screening and spin-dependent conductivity as sources of the spin accumulation in the model, the latter is neglible since interface effects play dominant role in the considered system. For the interaction between spin accumulation and magnetization at interfaces we applied the continuous approach for the spin-transfer torque 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%